2021
DOI: 10.1002/acr.24195
|View full text |Cite
|
Sign up to set email alerts
|

Most Appropriate Conventional Disease‐Modifying Antirheumatic Drug to Combine With Different Advanced Therapies in Rheumatoid Arthritis: A Systematic Literature Review With Meta‐Analysis

Abstract: Objective In rheumatoid arthritis, the association between advanced therapies (including biologic disease‐modifying antirheumatic drugs [DMARDs] and targeted synthetic DMARDs) and methotrexate (MTX) is recommended by international societies. When MTX cannot be used, other conventional synthetic DMARDs (csDMARDs) may be proposed. We aimed to compare the safety and efficacy of MTX and non‐MTX csDMARDs in combination with advanced therapies. Methods We systematically searched the literature for studies comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
1
0
2
Order By: Relevance
“…Similar reassuring results were observed when combining leflunomide with anti-TNF, abatacept or rituximab. 31 Studies have confirmed that methotrexate-leflunomide combination therapy is safe and well tolerated 32 in patients with refractory RA. There are no recent publications looking at the safety and efficacy of methotrexateazathioprine and methotrexate-cyclosporin combination therapy but a Cochrane review found an increased risk of predominantly gastrointestinal adverse events in the combination groups but did not appear to show an increase in infection.…”
Section: Combination Therapymentioning
confidence: 96%
“…Similar reassuring results were observed when combining leflunomide with anti-TNF, abatacept or rituximab. 31 Studies have confirmed that methotrexate-leflunomide combination therapy is safe and well tolerated 32 in patients with refractory RA. There are no recent publications looking at the safety and efficacy of methotrexateazathioprine and methotrexate-cyclosporin combination therapy but a Cochrane review found an increased risk of predominantly gastrointestinal adverse events in the combination groups but did not appear to show an increase in infection.…”
Section: Combination Therapymentioning
confidence: 96%
“…Im Falle einer MTX-Aversion kommt alternativ auch Leflunomid in Betracht. Eine Metaanalyse konnte hinsichtlich Wirksamkeit und Sicherheit der Kombination von Abatacept mit Leflunomid bei Patienten mit RA keine Unterschiede im Vergleich zu MTX nachweisen 9 . Die Kombination von Biologika und JAK-Inhibitoren wird aufgrund einer potenziellen schweren Immunsuppression bei Blockade mehrerer Signalwege und des unklaren Nebenwirkungsprofils kritisch gesehen.…”
Section: Diskussionunclassified
“…To właśnie A771726 (czynny metabolit leflunomidu) hamuje aktywność występującego u ludzi enzymu dehydrogenazy dihydroorotanu (DHODH) i wykazuje właściwości przeciwproliferacyjne i immunosupresyjne [3]. [10]. Leflunomid daje więc duże możliwości terapeutyczne w monoterapii i politerapii, zarówno w pierwszej, jak i kolejnych liniach leczenia chorób reumatycznych.…”
Section: Mechanizm Działania Leflunomiduunclassified